Trust towards zakat institutions among muslims business owners - Muhammad Ridhwan AB. Aziz; Nur Aqilah Hazirah Mohd Anim (Faculty of Economics, Universitas Islam Indonesia, 2024)
This study aims to examine the antecedents of zakat payers’ trust among Muslim business owners in Negeri Sembilan, Malaysia to make direct payment of zakat through zakat institutions. Three factors were proposed, which are board capital composition, disclosure practice and stakeholder management. This research is a quantitative research whereby 97 questionnaires among business owners in the sector of food and beverages were collected and analysed using multiple regression analysis. The finding revealed that disclosure practice and stakeholder management have a significant relationship with trust. This indicates that zakat institutions are urged to be transparent in their management especially in terms of financial disclosure to their stakeholder. This study helps in ensuring optimal proficiency of zakat institutions and maximization of zakat benefit to the widest possible range of eligible recipients.